2006
DOI: 10.1897/05-105r.1
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural soils spiked with copper mine wastes and copper concentrate: Implications for copper bioavailability and bioaccumulation

Abstract: A better understanding of exposure to and effects of copper-rich pollutants in soils is required for accurate environmental risk assessment of copper. A greenhouse experiment was conducted to study copper bioavailability and bioaccumulation in agricultural soils spiked with different types of copper-rich mine solid wastes (copper ore, tailing sand, smelter dust, and smelter slag) and copper concentrate. A copper salt (copper sulfate, CuSO4) that frequently is used to assess soil copper bioavailability and phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…The soil C-had adverse effects on the growth of ryegrass plants, reducing both the shoot biomass production (Figure 1) and the root cover (Figure 2) by 71% and 61%, respectively, when compared to the productivity reached in the soil C+. The same phytotoxicity results have been described for other plant species grown on soils artificially spiked with copper smelter dust (Sauvé et al, 2000;Ginocchio et al, 2006). In general, high metal-toxicity has been found in soils polluted with metal smelter dust, irrespective of the soil type (i.e.…”
Section: Plant Responses To Experimental Substratessupporting
confidence: 73%
“…The soil C-had adverse effects on the growth of ryegrass plants, reducing both the shoot biomass production (Figure 1) and the root cover (Figure 2) by 71% and 61%, respectively, when compared to the productivity reached in the soil C+. The same phytotoxicity results have been described for other plant species grown on soils artificially spiked with copper smelter dust (Sauvé et al, 2000;Ginocchio et al, 2006). In general, high metal-toxicity has been found in soils polluted with metal smelter dust, irrespective of the soil type (i.e.…”
Section: Plant Responses To Experimental Substratessupporting
confidence: 73%
“…In addition to the human wealth and welfare associated with this activity, it has generated intense environmental degradation through the production of a broad range of hard-rock residues, such as tailing storage facilities, heap leach piles, and smelter dust and slags (Asami 1988, Dudka & Adriano 1997. Abandoned tailing storage facilities (TSFs), for instance, are a potential source of pollution given their high metal concentrations (Badilla-Ohlbaum et al 2001, Frérot et al 2006, Ginocchio et al 2006. Loose tailings particulate matter is easily mobilized by wind, rain, and landslides, altering stream and soil quality, thus posing risks for crops, animal husbandry, wildlife, and human health (Petrisor et al 2004, Mendez & Maier 2008.…”
Section: Introductionmentioning
confidence: 99%
“…F144), noting total yield, fruit number, dry root weight, and plant height decreased with increasing application rate. Ginocchio et al (2006) showed that above ~ 300 mg Cu kg -1 lettuce (Lactuca sativa var. capitata) yield began to decrease.…”
Section: Alfalfa Et Growth and Alfalfa Cu Concentrationmentioning
confidence: 99%